Comparative Study of The Sustainability Transport Systems - Jenny Jenny; Andri Irfan Rifai; Susanty Handayani (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Compare of the sustainability transportation systems between Indonesia and Germany. Learning implements some lessons learned from the German experience to the development of transportation planning in Indonesia to support sustainable land use and transportation by comparing and analyzing the probability of converting and adopting reducing private transportation, landscape, financing mechanisms, and transport mechanism between Germany and Indonesia. Design/methodology/approach: Analyzing obtained data based on the comparison's parameters framework. Findings: Potentially, a parameter that can be set to develop a better transportation system for environmental and people safety, or even to reduce the congestion that occurs in most of Indonesia's metropolitan areas. Research limitations/implications: Since the study location is in fact somewhat distant, the information that is gathered to analyze the comparison is only chosen from each country's broad outline and is not otherwise specified. Practical implications: Finding solution for a better sustainable transportation in Indonesia that can be implemented. Originality/value: The analytical framework that is implemented in this comparative study is a methodically innovative approach form of developing an Innovative Transport System that is to aim a better use of transport network. Paper type: Literature Review